The semantics of degree words In english vs vietnamese - Nguyễn Phước Trâm Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aimed to discover the syntactic and semantic aspects of Degree words in English and Vietnamese. We examined a great variety of linguistic devices functioning to investigate the people’s degree words which existed in structure of Degs in both languages. This qualitative study was carried out in a contrastive analysis with English as the target language and Vietnamese as source one. The reference to X – Bar theory was aimed at defined the syntactic position of Degs in the architecture of the larger units in which they occur . And from the context of utterance, the semantic features of Degs could be found out. The samples defined as instances of Degs in utterances containing degree words randomly were picked out from the population of 400 utterances modified with degree words ( 200 in English and 200 in Vietnamese ). The drawings from findings help Vietnamese learners of English use degree words effectively in their concrete communication situations.